Impacts of completely endophytic renal masses on perioperative, oncologic, and functional outcomes in robot-assisted partial nephrectomy: a systematic review and meta-analysis - Gu, Han-xiao; Lv, Jia; Liu, Yi (Frontiers in Oncology, 2024)
BackgroundThe objective of this study was to perform a comprehensive pooled analysis aimed at comparing the efficacy and safety of robot-assisted partial nephrectomy (RAPN) between completely endophytic tumors (CERT) and non-completely endophytic tumors (non-CERT).MethodsThis study adhered rigorously to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to conduct a systematic review and meta-analysis. We performed a systematic search in the PubMed, Embase, Web of Science, and Cochrane Library databases, focusing on studies published in English up to May 2024. Our analysis primarily evaluated key outcomes, specifically perioperative, functional, and oncological outcomes.ResultsA total of 2126 patients across six studies were included in the analysis. Compared to non-CERT, CERT was associated with significantly higher rates of major complications (Odds Ratio [OR]: 2.47; 95% CI: 1.14 to 5.34; p = 0.02), longer warm ischemia times (Weighted Mean Difference [WMD]: 3.27 min; 95% CI: 0.61 to 5.39; p = 0.02), a greater decline in estimated glomerular filtration rate (eGFR) (WMD: 2.93 ml/min/1.73 m2; 95% CI: 0.75 to 5.11; p = 0.008), and relatively lower trifecta achievement rates (OR: 0.63; 95% CI: 0.41 to 0.96; p = 0.03). However, no statistically significant differences were observed between the two groups in terms of operative time, length of stay, blood loss, transfusion rates, intraoperative complications, overall complications, positive surgical margins, and local recurrence.ConclusionsAlthough CERT was associated with greater declines in eGFR and lower rates of trifecta achievement, it yielded perioperative, functional, and oncologic outcomes comparable to those of non-CERT in RAPN. Our findings suggest that RAPN for completely endophytic renal masses can achieve acceptable outcomes when performed in centers with substantial expertise in robotic surgery.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=555067, identifier CRD42024555067.